New coordinated drive mode switching strategy for distributed drive electric vehicles with energy storage system - Adel Oubelaid; Khoudir Kakouche; Youcef Belkhier; Nima Khosravi; Nabil Taib; Toufik Rekioua; Mohit Bajaj; Djamila Rekioua; Milkias Berhanu Tuka (Scientific Reports, 2024)
Abstract High performance and comfort are key features recommended in hybrid electric vehicle (HEV) design. In this paper, a new coordination strategy is proposed to solve the issue of undesired torque jerks and large power ripples noticed respectively during drive mode commutations and power sources switching. The proposed coordinated switching strategy uses stair-based transition function to perform drive mode commutations and power source switching’s within defined transition periods fitting the transient dynamics of power sources and traction machines. The proposed technique is applied on a battery/ supercapacitor electric vehicle whose traction is ensured by two permanent magnet synchronous machines controlled using direct torque control and linked to HEV front and rear wheels. Simulation results highlight that the proposed coordinated switching strategy has a noteworthy positive impact on enhancing HEV transient performance as DC bus fluctuations were reduced to a narrow band of 6 V and transient torque ripples were almost suppressed.